HIGHWAY WIDENING AND REINFORCING USING ADAPTABLE PAVEMENT DESIGN - Tanwer, M. Tamim; Pandey, Anchal U.; Dhimmar, Devanshu (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The rapid growth of traffic parallels population and living standards, leading to congestion, noise, and air pollution. Increased travel times and fuel consumption accompany these challenges, affecting car independence, comfort, and convenience, while service levels decline. Therefore, it is crucial to enhance existing road lanes by widening them to accommodate increasing traffic volumes. Strengthening and widening the roads will improve service quality, reduce vehicle maintenance needs, decrease travel time, and lower fuel consumption. Ultimately, this enhances passenger services and ensures safer transportation options. Reducing gasoline usage would result in less pollution and a cleaner environment. Smooth traffic flow enhances user convenience, comfort, and improves the aesthetics of roads. The proposed project is recommended for the Vasad to Tarapur SH-8 route, which currently features a flexible pavement design. There is heavy traffic congestion with numerous buses, cars, and commercial vehicles, leading to deteriorating road conditions and poor ride quality. The state highway project, based on Design, Build, Finance, and Operate (DBFO) principles, is improving the 51-kilometer Vasad-Tarapur route. Initially a three-lane road with a 12-meter width, it is being expanded to a six-lane toll road. Funding from the World Bank and commercial financial institutions supports this initiative, aiming to upgrade the existing three-lane highways in line with IRC 81-1997 standards. The current three-lane road will be paralleled by the three-lane road that will be widened to six lanes. According to IRC 37-2001, the flexible pavement design for the proposed pavement is 610mm.The construction process and material selection criteria are applied for quality control. We’ll poll people’s willingness to pay for the proposed toll road, and we’ll declare toll prices in accordance with government regulations.